Evolution of flow fields in a developing local scour hole formed by a submerged wall jet - Si, Jin-Hua (2022)
This study investigates the flow in an evolving scour hole downstream of a sluice gate with an apron using particle image velocimetry (PIV). The results clearly depict the sequential appearance of four rollers (large vortices) and the evolving connections between the 1st-order moment (velocity) and the 2nd-order moments (turbulent kinetic energy and Reynolds shear stress), during the three-stage (early, intermediate and equilibrium) scour process. At any scour stage, the velocity profiles on cross-jet sections exhibit global self-similarity, whereas those along the jet centerlines preserve self-similarity local to regions with significant average kinetic energy (AKE). Both the profile of the scour hole and the flow fields share self-similarity in terms of spatial distribution, when normalized with proper length and velocity scales. A substantial portion of energy is transferred from the fluid phase to the sediment phase as one of the primary factors for scour upon the incoming jet impinging on the bed, whereas turbulence is merely a secondary factor.